Analysis of Factors Influencing Premarital Sexual Behavior in Adolescents Reviewed from Transcultural - Sinambela, Sunggulan; Prasetyo, Joko; Peristiowati, Yuly (GLOBAL HEALTH SCIENCE GROUP, 2024)
Sex pre-marriage among teenagers is Already at alarming levels in cities in Indonesia. Contributing factors _ behavior sex pre-wedding which is factor knowledge, support of social and family, religiosity, technology, and values culture. Sex pre-wedding happens in various ways ethnicity, religion, and culture. Toba Batak is a philosophical tribe _ obedient to norms laws and custom customs. Or customs that are based/supported by the customs and teachings of the Christian religion in his teachings forbid adulterous activities. Objective of study This For know related factors _ with behavior sex pre-marriage among teenagers at SMA N Toba Regency. Method: The method study uses cross cross-sectional method and sample in the study which is 152 teenagers. Data collection using a questionnaire and data tested with Chi-Square (α<0.05). Research results show that No there is the relationship between value culture and style of life (p=.528), support family and social (p=.976), religiosityand philosophy (.358) technology (p=.002), knowledge (.464), and attitude (.629).